The Evaluation of Dissolved Oxygen (DO), Total Suspended Solids (TSS) and Suspended Sediment Concentration (SSC) in Terengganu River, Malaysia - Abd Wahab, Noorjima; Khairul Amri Kamarudin, Mohd; Ekhwan Toriman, Mohd; Marcus Ata, Frankie; Juahir, Hafizan; Ghazali, Adiana; Anuar, Atikah (International Journal of Engineering and Technology, 2018)
Terengganu River Basin is situated in the north eastern coastal region of Peninsular Malaysia. 29 sampling stations were selected. The water quality parameters were measured such as Dissolved Oxygen (DO), Total Suspended Solids (TSS) and Suspended Sediment Concentration (SSC). Results showed that the range of DO (2.11 mg/L – 8.07 mg/L), TSS (0.4 mg/L – 128.2 mg/L) and SSC (0.07 mg/L – 25.6 mg/L). The distribution of land use and land cover activities effected to the level of water quality in watersheds. The analyses of variance (ANOVA) was applied and provide a better understanding for the complex relationships among water quality parameters. Graphical data helps a better view of the overall analysis to appoint sources of pollutants to their effect. Terengganu River Basin is a shallow and has a sensitive ecosystem that responds to the land use changes and development activities of its surroundings. Water quality analysis showed that TSS and SSC were higher in the dry season but DO were higher in the wet season. Overall, the water in the Terengganu River Basin classified slightly contaminated especially the main sources of pollutants were possibly waste products and waste from development activities such as sand mining, farming, residential and agricultural.